Long‐term metformin use reduces gastric cancer risk in type 2 diabetics without insulin treatment: a nationwide cohort study. Issue 8 (20th February 2014) - Kim, Y.‐I.; Kim, S. Y.; Cho, S.‐J.; Park, J.‐H.; Choi, I. J.; Lee, Y. J.; Lee, E. K.; Kook, M.‐C.; Kim, C. G.; Ryu, K. W.; Kim, Y.‐W.
Summary Background Metformin use has been associated with a decreased incidence and mortality of various cancers. Aim To evaluate the association between metformin use and gastric cancer. Methods We randomly selected 100 000 type 2 diabetic patients from the 2004 Korean National Health Insurance claim database, and assessed gastric cancer incidence among 39 989 patients (aged 30–97 years) who were regularly treated with anti‐diabetic drugs and followed‐up from 2004 to 2010. In total, 26 690 patients had used metformin out of 32 978 diabetics who had not regularly used insulin (insulin non‐users), and 5855 patients had used metformin out of 7011 regular insulin users. Results Patients who used metformin showed a lower incidence of gastric cancer than those who did not use metformin, in insulin non‐users (P = 0.047, log‐rank test). However, in patients on regular insulin, there was no difference of gastric cancer incidence according to metformin use. In insulin non‐users, the adjusted hazard ratio (AHR) for metformin use was 0.73 (95% confidential interval [CI], 0.53–1.01) with borderline statistical significance (P = 0.059). Duration of metformin use was associated with the reduction in gastric cancer risk (AHR, 0.88; 95% CI 0.81–0.96, P = 0.003), especially in patients who used metformin for more than 3 years (AHR, 0.57; 95% CI, 0.37–0.87; P = 0.009). Conclusion Metformin use >3 years in type 2 diabetics who do not use insulin is associated with a significantly reduced gastric cancer risk.